Improve the working enviroment at Sunjin Vietnam joint venture Company - Nguyen, Viet Cuong (Khoa Quốc tế, ĐHQGHN, 2020)
This dissertation is developed under the context of Sunjin Vietnam is now focusing on the improvement of working condition and paying special attention to a performance culture that values every single employee and promotes a sustainable work-life balance should be embraced. Some research objectives are proposed and they are to identify the relationship between Sunjin’s employees’ performance and different aspects of workplace environment and to propose the solutions to improve workplace environment and to obtain higher employees’ performance